PENGARUH PROFITABILITY, LEVERAGE DAN CAPITAL INTENSITY PERUSAHAAN DI BEI TERHADAP TAX - Mianti; Santioso, Linda (Jurnal Paradigma Akuntansi, 2025)
The purpose was conducted to find out how influential profitability, financial leverage, capital intensity to tax avoidance. The data used in this study is secondary data from companies in the raw goods and health sectors that are listed on the BEI in 2019-2021. The sample is formed a purposive sampling and 34 companies were obtained. The data was processed using SPSS version 16 software. According from this study, financial leverage has a negative and significant influential to tax avoidance. Meanwhile, profitability, capital intensity have a negative and insignificant influential to tax avoidance.